Security in Wireless Sensor Networks - Oreku, George S.; Pazynyuk, Tamara; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2016)
This monograph covers different aspects of sensor network security including new emerging technologies. The authors present a mathematical approach to the topic and give numerous practical examples as well as case studies to illustrate the theory. The target audience primarily comprises experts and practitioners in the field of sensor network security, but the book may also be beneficial for researchers in academia as well as for graduate students.
Introduction and Overview -- QoS as Means of Providing WSN Security -- Mathematical Model for Wireless Sensor Nodes Security -- Improved Feistel-based Ciphers for Wireless Sensor Network Security -- The Distributed Signature Scheme (DSS) Based on RSA -- Reliable Data Aggregation Protocol for Wireless Sensor Networks -- Conclusions and Future Work.
Keywords: Telecommunication; Computer science -- Mathematics; Computer networks .; Graph theory; Security systems; Communications Engineering, Networks; Mathematical Applications in Computer Science; Computer Communication Networks; Graph Theory; Security Science and Technology